2019
DOI: 10.1002/wrna.1535
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular RNA in viral–host interactions: Thinking outside the cell

Abstract: Small RNAs and their associated RNA interference (RNAi) pathways underpin diverse mechanisms of gene regulation and genome defense across all three kingdoms of life and are integral to virus–host interactions. In plants, fungi and many animals, an ancestral RNAi pathway exists as a host defense mechanism whereby viral double‐stranded RNA is processed to small RNAs that enable recognition and degradation of the virus. While this antiviral RNAi pathway is not generally thought to be present in mammals, other RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 213 publications
(290 reference statements)
1
11
0
Order By: Relevance
“…In systemic alteration of an immune response, major regulators commonly known as specifically enriched micro RNAs (miRNAs) are delivered by EVs. These are loaded into EVs and are involved in post-transcriptional regulation of gene expression, which is known to be influential for HCV replication [176,177]. This confirms that EVs have peculiar miRNA expression isolated from the sera of chronic HCV patients.…”
Section: Hepatitis C Virus and Evssupporting
confidence: 53%
“…In systemic alteration of an immune response, major regulators commonly known as specifically enriched micro RNAs (miRNAs) are delivered by EVs. These are loaded into EVs and are involved in post-transcriptional regulation of gene expression, which is known to be influential for HCV replication [176,177]. This confirms that EVs have peculiar miRNA expression isolated from the sera of chronic HCV patients.…”
Section: Hepatitis C Virus and Evssupporting
confidence: 53%
“…They are released by donor cells into their surrounding environment. EVs have been extensively characterized in animals and humans, where they are classified based on their size and origins: exosomes, which are 30 to 100 nm in diameter; shedding microvesicles, which are 100 nm to 1 mm in diameter; and apoptotic bodies, which are 50 nm to 5 mm in diameter (Théry et al, 2009;Ressel et al, 2019). Microvesicles are shed from the plasma membrane; apoptotic bodies contain parts of dying cells formed during programmed cell death; and exosomes are formed in the cytosol by inward budding of the limiting membrane of endocytic compartments, leading to vesicle-containing endosomes called multivesicular bodies (MVBs).…”
Section: Mechanism(s) Of Srna Movement Between Pathogens and Plant Cellsmentioning
confidence: 99%
“…Microvesicles are shed from the plasma membrane; apoptotic bodies contain parts of dying cells formed during programmed cell death; and exosomes are formed in the cytosol by inward budding of the limiting membrane of endocytic compartments, leading to vesicle-containing endosomes called multivesicular bodies (MVBs). The vesicles are released into the environment when MVBs fuse with the plasma membrane (Raposo and Stoorvogel, 2013;Ressel et al, 2019). EVs have been shown to be key players in intercellular communication in animal systems.…”
Section: Mechanism(s) Of Srna Movement Between Pathogens and Plant Cellsmentioning
confidence: 99%
“…We found that T. vaginalis EVs deliver proteins and RNA into host cells via unknown mechanisms and modulate parasite adherence to host cells and host cell metabolism (14,15). EVs produced by several parasites have now been described to module host cell metabolism in many ways (16)(17)(18)(19), including the transfer of virulence factors (20), drug resistance markers (21), and microRNAs that downregulate host cell proteins (22)(23)(24). Pathogen EVs have also been shown to affect host cell proliferation (24,25) and neuronal metabolism (26) and to modulate host immune responses (17,23,24,(27)(28)(29).…”
mentioning
confidence: 99%